Establishment of Human Neural Progenitor Cells from Human Induced Pluripotent Stem Cells with Diverse Tissue Origins. (26th April 2016) - Fukusumi, Hayato; Shofuda, Tomoko; Bamba, Yohei; Yamamoto, Atsuyo; Kanematsu, Daisuke; Handa, Yukako; Okita, Keisuke; Nakamura, Masaya; Yamanaka, Shinya; Okano, Hideyuki; Kanemura, Yonehiro
Abstract : Human neural progenitor cells (hNPCs) have previously been generated from limited numbers of human induced pluripotent stem cell (hiPSC) clones. Here, 21 hiPSC clones derived from human dermal fibroblasts, cord blood cells, and peripheral blood mononuclear cells were differentiated using two neural induction methods, an embryoid body (EB) formation-based method and an EB formation method using dual SMAD inhibitors (dSMADi). Our results showed that expandable hNPCs could be generated from hiPSC clones with diverse somatic tissue origins. The established hNPCs exhibited a mid/hindbrain-type neural identity and uniform expression of neural progenitor genes.